Risk for Behavioral Problems Independent of Cognitive Functioning in Children Born at Low Gestational Ages - Domellöf, Erik; Johansson, Anna-Maria; Farooqi, Aijaz; Domellöf, Magnus; Rönnqvist, Louise (Frontiers in Pediatrics, 2020)
This study aimed to investigate cognitive and behavioral outcomes in relation to gestational age (GA) in school-aged children born preterm (PT). Results from the Wechsler Intelligence Scale for Children, 4th edition (WISC-IV), and the Child Behavior Checklist (CBCL) were analyzed in 51 children (mean age: 7.8 years [range: 7.0–8.7]) born PT (mean GA: 31 weeks [range: 23–35]; birth weight, mean: 1,637 g [range: 404–2,962]) with the majority (96%) having no diagnosed cognitive, sensory, or motor impairments. The control group included 57 age-matched typically developing children (mean age: 7.9 years [range: 6.2–8.7]) born full-term (FT). Children born PT, extremely PT (GA < 28) in particular, showed significantly lower cognitive performance and higher behavioral problem scores compared with children born FT. GA was found to predict aspects of both cognitive functioning and behavioral problems within the PT group, with lower GA being related to both poorer cognitive outcomes and elevated affective and attention-deficit/hyperactivity problems. Global cognitive functioning did not independently predict aspects of behavioral outcomes. Findings demonstrate that, even in children born PT without severe perinatal and/or postnatal complications and receiving active perinatal care, a short gestation is an evident risk factor for long-term negative effects on mental health independent of cognitive functioning. Additional findings suggest that both reduced growth and lower parental educational level may contribute to increased risk for poorer cognitive and behavioral functioning in children born PT.